2021
DOI: 10.1111/aogs.14221
|View full text |Cite
|
Sign up to set email alerts
|

Paternal age over 50 years decreases assisted reproductive technology (ART) success: A single UK center retrospective analysis

Abstract: Introduction: To study whether paternal age exerts an effect, independent of maternal age, on the outcomes of fresh in vitro fertilization/ intracytoplasmic sperm injection (IVF/ICSI) cycles. Semen quality deteriorates with increasing paternal age; however, there is conflicting evidence for any impact paternal age may have on the outcome of IVF/ICSI. Several retrospective and prospective cohort studies have shown that paternal age increases the miscarriage rate and reduces the live birth rate. Some studies hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“… 46 The results of a British study showed that paternal age over 50 years decreased the success rate of ART. 47 However, some studies have shown that paternal age was not associated with adverse IVF outcomes. 48 , 49 In this study, paternal age was not associated with pregnancy failure after ART in infertile patients.…”
Section: Discussionmentioning
confidence: 99%
“… 46 The results of a British study showed that paternal age over 50 years decreased the success rate of ART. 47 However, some studies have shown that paternal age was not associated with adverse IVF outcomes. 48 , 49 In this study, paternal age was not associated with pregnancy failure after ART in infertile patients.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced paternal age has been associated with various adverse outcomes with assisted reproductive technologies (ARTs) including poor embryo quality, increased miscarriage rates, reduced fertilization, implantation, pregnancy, and live birth rates ( 40 48 ). Inconsistency and conflicting data exist ( 49 51 ) likely due to the results of confounders and bias in the design of the studies, small sample size, retrospective nature and heterogeneity of the subjects.…”
Section: Impact Of Advanced Paternal Age In Men and On Their Progenymentioning
confidence: 99%
“…However, there were no significant differences in live birth or miscarriage where the female partner was < 35 years of age [ 91 ]. A single centre retrospective cohort study of 4833 ART cycles involving 4271 men reported also significantly lower probability of live birth with paternal age > 50 years [ 92 ]. In a recent meta-analysis, data extracted from 28 studies (16 autologous oocyte studies; 12 donor oocyte studies) were collated to analyse the effect of paternal age at 30–50 years.…”
Section: Assisted Reproduction Technology Outcomesmentioning
confidence: 99%